Closing Rice Yield Gaps in Asia: Innovations, Scaling, and Policies for Environmentally Sustainable Lowland Rice Production - Connor, Melanie; Gummert, Martin; Singleton, Grant Robert (Springer, 2023)
This book contains key lessons learned from CORIGAP, such as detailed documentation of the implementation, dissemination, and impact of the CORIGAP project. It presents actionable research findings with the experience of bringing these findings into use. It provides a wide array of pathways to impact sustainable rice production in lowland irrigated rice-based agricultural systems.